2011
DOI: 10.1371/journal.pone.0026708
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Dream-Lag Effect for REM and NREM Stage 2 Dreams

Abstract: This study investigates evidence, from dream reports, for memory consolidation during sleep. It is well-known that events and memories from waking life can be incorporated into dreams. These incorporations can be a literal replication of what occurred in waking life, or, more often, they can be partial or indirect. Two types of temporal relationship have been found to characterize the time of occurrence of a daytime event and the reappearance or incorporation of its features in a dream. These temporal relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 43 publications
3
61
1
1
Order By: Relevance
“…This is in keeping with both the day residue (Freud, 1900;Nielsen & Powell, 1992;Powell, Nielsen, Cheung, & Cervenka, 1995), and dream lag (Blagrove et al, 2011a(Blagrove et al, , 2011bNielsen, Kuiken, Alain, Stenstrom, & Powell, 2004) effects. Analyses in the present study illustrated the predominance of waking-life interpersonal relationships being represented in dreams, and to a lesser extent but still common waking-life concerns about work or studying, but financial worries in dreams were relatively rare.…”
Section: Discussionsupporting
confidence: 80%
“…This is in keeping with both the day residue (Freud, 1900;Nielsen & Powell, 1992;Powell, Nielsen, Cheung, & Cervenka, 1995), and dream lag (Blagrove et al, 2011a(Blagrove et al, , 2011bNielsen, Kuiken, Alain, Stenstrom, & Powell, 2004) effects. Analyses in the present study illustrated the predominance of waking-life interpersonal relationships being represented in dreams, and to a lesser extent but still common waking-life concerns about work or studying, but financial worries in dreams were relatively rare.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, Blagrove et al (2011) demonstrated that the dream-lag effect was evident in REM but not NREM dreams, potentially demonstrating time of night effects also. In the present study, power analyses suggest that the small sample sizes may account for the null finding; however, Hall (1966, cited in Domhoff, 2003 did not replicate Verdone's findings, and significant results were found for other analyses with small samples in the present study, so this matter is still unresolved and is certainly worthy of further investigation.…”
Section: The Effect Of Time Of Night On Time Referentsmentioning
confidence: 84%
“…() have shown that the dream‐lag effect is not a result of confounding of the incorporation of weekly recurring events, where day‐residue incorporations of these might spuriously appear to refer to events from the previous week. The dream‐lag effect has been found using naturalistic events that occur in the participants' daily lives (Blagrove, Fouquet et al., ; Blagrove, Henley‐Einion et al., ; Nielsen et al., ; Nielsen & Powell, , experiment 1; van Rijn et al., , experiment 1, home dreams condition) and using standardized stimulus designs with stimuli such as a night sleeping in the sleep laboratory (Nielsen & Powell, , experiment 2; van Rijn et al., , experiment 2) or the watching of an emotionally arousing videotape of an animal sacrifice (Powell, Nielsen, Cheung, & Cervenka, ).…”
Section: Introductionmentioning
confidence: 99%